2009
DOI: 10.1093/cercor/bhp251
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Modulation Differs between Basal and Apical Dendritic Excitation of Hippocampal CA1 Pyramidal Cells

Abstract: We hypothesize that endogenous cholinergic modulation of dendritic processing of hippocampal CA1 is layer specific, and it specifically enhances spike output resulting from basal as compared with the apical dendritic excitation. Laminar profiles of evoked field potentials were recorded in the CA1 area of urethane-anesthetized rats using multichannel silicon probes and analyzed as current source density. High-frequency stimulation of the pontis oralis (PnO) attenuated the midapical more than the basal or distal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 85 publications
6
25
0
Order By: Relevance
“…The results below were presented for the negative fEPSP at the stratum oriens electrode, which was directly generated by the basal-dendritic excitatory sink in CA1 (Leung and Peloquin, 2010). Because the basal-dendritic fEPSP manifests a dipole field, similar results on LTP were found for the stratum radiatum electrode (supplemental Fig.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The results below were presented for the negative fEPSP at the stratum oriens electrode, which was directly generated by the basal-dendritic excitatory sink in CA1 (Leung and Peloquin, 2010). Because the basal-dendritic fEPSP manifests a dipole field, similar results on LTP were found for the stratum radiatum electrode (supplemental Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Combined with our previous demonstration that selective lesion of cholinergic neurons in the medial septum with 192IgG-saporin also abolished the facilitation of LTP by walking (Leung et al, 2003), the most parsimonious model consistent with the literature is that histamine excites cholinergic septohippocampal neurons to increase ACh release in the hippocampus. ACh, in turn, may facilitate basal-dendritic LTP by increasing spiking after basal-dendritic excitation (Leung and Peloquin, 2010) or by enhancing NMDA receptor-mediated current (Markram and Segal, 1992;Marino et al, 1998).…”
Section: Ltp and Histaminementioning
confidence: 99%
“…The figures will present only the negative fEPSPs recorded at the alveus/stratum oriens electrode, which was directly generated by a basal dendritic excitatory sink in CA1 [49].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have implicated M1 (Kremin et al 2006;Leung and Péloquin 2010;Sheridan and Sutor 1990;Shinoe et al 2005), M2 (Dutar and Nicoll 1988;Segal 1989), and M4 receptors (Shirey et al 2008) as mediating cholinergic suppression of glutamate release. We found that M4 receptors are required for normal cholinergic suppression of synaptic transmission at the Schaffer-collateral synapse.…”
Section: Cholinergic Suppression Of Excitatory Synaptic Transmissionmentioning
confidence: 99%
“…Cholinergic suppression of synaptic transmission is mediated by mAChRs, but the available data are inconclusive as to the receptor subtype(s) involved. At the Schaffer-collateral synapse, data exist implicating M1 (Kremin et al 2006;Leung and Péloquin 2010;Sheridan and Sutor 1990;Shinoe et al 2005), M2 (Dutar and Nicoll 1988;Seeger et al 2004;Segal 1989), and M4 (Shirey et al 2008) receptors.…”
Section: Introductionmentioning
confidence: 99%